Decision support systems and intelligent systems - Turban, Efraim (Prentice Hall, 2005)
Decision Support Systems and Intelligent Systems, Seventh Edition is a comprehensive, up-to-date guide to todays revolutionary management support system technologies, and how they can be used for better decision making. In this thoroughly revised edition, the authors go far beyond traditional "decision support systems," focusing far more coverage on Web-enabled tools, performance analysis, knowledge management, and other recent innovations. The authors introduce each significant new technology, show how it works, and offer practical guidance on integrating it into real-world organizations. Examples, products, services, and exercises are presented throughout, and the text has been revised for improved clarity and readability. New and enhanced coverage includes: state-of-the-art data mining, OLAP, expert system, and neural network software; revamped coverage of knowledge management; and a far greater emphasis on the use of Web technologies throughout. Also covered in detail: data warehousing, including access, analysis, visualization, modeling, and support. This edition also contains DSS In Action boxes presenting real business scenarios for the use of advanced management support technology. Decision Support Systems and Intelligent Systems, Seventh Edition is supported by a Web site containing additional readings, relevant links, and other supplements.